Evaluation of the possible life of pear (Packham’s Triumph) through coating with carnauba wax and bee wax - García Miranda, Hugo Rafael (2019)
The study of the application of coatings on the pear is very scarce, for this reason the research aimed to "Evaluate the effect of beeswax and carnauba wax on the post-harvest life of pear (Packham's triumph)" The evaluation was carried out at the Universidad Privada de Tacna, Laboratory for the analysis of agroindustrial products. For this, carnauba wax and beeswax were used. Through previous experiments, treatments with beeswax (TCA), with carnauba wax (TCC) and a mixed treatment (TM, "beeswax and carnauba wax") were formulated, where it was found that the coating with greater fuel stability mix 40 % beeswax and 60% carnauba wax, for analysis purposes the parameters needed to measure were identified, such as total soluble solids (SST), titratable acidity, pH, weight, color, CO_2 and Firmness Concluding that the mixture treatment (TM, “beeswax 40% and carnauba wax 60%”) had better results, increased the useful life in an additional five and six days, the data obtained at 17 days of study were, strongly Total soluble (11.3 ° brix), titratable acidity (0.0415%), pH (4.98), weight (13.48%), color (greenish brown), CO_2 (27352.59 mg. CO_2 /Kg.h) and Firmness (2.54 N).